REKONSTRUKSI “ISLAM TEH SUNDA, SUNDA TEH ISLAM” - Abdurrahman MBP (Asy-Syari'ah, 2015)
This paper describes the background of the “Islam teh Sunda dan Sunda teh Islam” means that “Islam is the same as the Sunda and Sunda that is Islam”, the term, was introduced by Haji Endang Saefudin Ansari. To know the term, the authors will focus on the discussion of the history of the emergence of the term “Islam teh Sunda dan Sunda teh Islam”, the development of the term “Islam teh Sunda dan Sunda teh Islam”, and the reconstruction of the term “Islam teh Sunda dan Sunda teh Islam”. The findings were obtained by the author of the term “Islam teh Sunda dan Sunda teh Islam”, namely: (1) the term “Islam teh Sunda dan Sunda teh Islam” is the reality of the Sundanese people who have accepted Islam because in harmony with the values of their kesundaan; (2) alignment of the Sunda and Islam looks of their belief in the existence of God the Creator and Owner of Nature (monotheism) as well as the behavior and ethics of Sunda in harmony with the manners and morals of Islam; and (3) Reconstruction of the term “Islam teh Sunda dan Sunda teh Islam” carried out by the foundation reaffirm tawhidullâh (belief in one Allah), build supporting pillars in the form of refund Hanif nature of mankind and formulate the roof as an umbrella that is fiqhiyyah rules especially rule “al-‘âdah al-muhakkamah”.